Titania supported bio-derived activated carbon as an electrode material for high-performance supercapacitors. (October 2021) - Bortamuly, Rajashree; Naresh, Vangapally; Das, Manash R.; Kumar, V. Kiran; Muduli, Sadananda; Martha, Surendra K.; Saikia, Pranjal
Highlights: Titania supported bio-derived, porous activated Carbon is used as electrode material. The specific capacitance of the C-TiO2 shows considerable improvement to pristine TiO2 . The composite material exhibits 92% of capacitance retention up to 5000 cycles. The capacitance of the C-TiO2 is a diffusion-controlled process. Abstract: Supercapacitors are promising energy storage devices compared to batteries due to their long cycle life and high-power density. In this work, we report a supercapacitor based on Titania supported bio-derived activated Carbon with high power density. The composite electrode material shows an initial specific capacitance of 214 F g −1 at 1 A g −1 and exhibits 92% of capacitance retention for 5000 cycles in 1 M Na2 SO4 solution. The enhanced electrochemical performance is due to the synergistic effect of the electric double-layer capacitance behavior of carbon and the pseudo-capacitive nature of Titania. An energy density of 29.72 and 20 Wh kg −1 can be achieved at a power density of 499 and 4000 W kg −1, respectively. The supercapacitor based on TiO2 based intercalation compounds provides significantly high energy at the expense of power, which may be appropriate for several applications.